A Self-Adaptive Agent-Based Dynamic Processes Simulation Modelling Framework - Loo Y.L.; Ahmad A.; Mustapha A.; Mostafa S.A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Adaptive algorithms; Agent based simulation; Agent-based simulation framework; Different domains; Domain specific; Dynamic process; Dynamic process simulation; Self-adaptive; Simulation framework; Simulation model; Simulation platform